Diffusion Study of Cream Formula of Lyophilized Ethanol Extract of Moringa oleifera L. Leaves : Studi Difusi Formula Krim Ekstrak Etanol Terliofilisasi Daun Kelor (Moringa oleifera L.) - Sapra, Amriani; Mus, Suwahyuni; Dwirandy, Dwirandy; Malluka, Rifka; Khairi, Nur (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2021)
Background: Moringa oleifera L. leaves have analgesic activity due to their flavonoids content. These polar antioxidants compounds usually have difficulty to diffuse through the skin. Objectives: The purpose of this study was to evaluate the diffusion parameters of cream contains the lyophilized of M. oleifera leaves ethanol extract. Material and Methods: The lyophilized of M.oleifera leaves ethanol extract (5%) formulated as an o/w cream with 2% of cetyl alcohol as a stiffening agent. The physical characteristics of the cream were determined for organoleptic, homogeneity, pH, viscosity, spreadability, and type of emulsion parameters. The diffusion parameters were determined with Franz cell diffusion using the skin's snake as a membrane with 0; 10; 30; 60 and 90 minutes sampling time. Results: Physical characteristics of the cream showed that o/w as the cream type with pH, viscosity, and spreadability value were 4.72±0.03; 14.000±225 cps; and 5.7±0.20 cm, respectively. The diffusion parameter showed total flavonoids penetrate through the membrane was 360.134±0.20 µg/cm2 with flux 239,875 µg/cm2hr. Conclusions: This study showed a cream formulation that fulfills the required physical characteristics standard and can deliver active compounds to penetrate through the membrane.